Fallopian tube catheterization in the treatment of proximal tubal obstruction: a systematic review and meta-analysis. Issue 4 (10th February 2017) - De Silva, P.M.; Chu, J.J; Gallos, I.D.; Vidyasagar, A.T.; Robinson, L.; Coomarasamy, A.
Abstract: STUDY QUESTION: What is the chance of clinical pregnancy when fallopian tube catheterization is used for proximal tubal obstruction? SUMMARY ANSWER: The pooled clinical pregnancy rate of tubal catheterization after proximal tubal obstruction is 27% (95% CI 25–30%). WHAT IS KNOWN ALREADY: Restoring fallopian tube patency by performing tubal catheterization has fallen out of favour since the increased availability of IVF. Our study is the first systematic review and meta-analysis to investigate reproductive outcomes following tubal catheterization for proximal tubal obstruction. STUDY DESIGN, SIZE, DURATION: We undertook a systematic review and meta-analysis of 27 observational studies consisting of 1720 patients undergoing tubal catheterization for proximal tubal obstruction, who attempted to conceive naturally after the procedure. PARTICIPANTS/MATERIALS, SETTING, METHODS: Systematic literature searches were performed in MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials. A total of 2195 titles and abstracts were reviewed. Only studies that reported outcomes when tubal catheterization was performed with no other tubal surgery were included. Twenty-seven cohort studies matched the inclusion criteria for the meta-analysis. MAIN RESULTS AND THE ROLE OF CHANCE: The meta-analysis showed a pooled clinical pregnancy rate of 27% (95% CI 25–30%) after the use of tubal catheterization for unilateral or bilateral proximal tubal obstruction (27 studies, 1556 patients). In women with bilateral obstruction (14 studies, 617 patients), the clinical pregnancy rate was 27% (95% CI 23–32%). Our meta-analysis demonstrated that the pooled cumulative clinical pregnancy rates were 22.3% (95% CI 17.8–27.8%) at 6 months, 25.8% (95% CI 21.1–31.5%) at 9 months, 26.4% (95% CI 23.0–30.2%) at 12 months, 26.0% (95% CI 22.8–29.7%) at 18 months, 27.0% (95% CI 24.0–30.5%) at 24 months, 27.9% (95% CI 24.9–31.3%) at 36 months and 28.5% (95% CI 25.5–31.8%) at 48 months. The pooled live birth rate (14 studies, 551 patients) was 22% (95% CI 18–26%). The pooled ectopic pregnancy rate (27 studies, 1556 patients) was 4% (95% CI 3–5%). The included studies scored satisfactorily on the Newcastle-Ottawa quality assessment scale. LIMITATIONS, REASONS FOR CAUTION: The pooled clinical pregnancy rate after tubal catheterization was found to be almost comparable to that after IVF. However, included studies were small, non-comparative series with significant clinical heterogeneity in population characteristics, follow-up and surgical equipment, technique and experience. WIDER IMPLICATIONS OF THE FINDINGS: These findings suggest fallopian tube catheterization as an alternative strategy to IVF in patients presenting with proximal tubal obstruction. Further research should focus on comparing different surgical techniques of fallopian tube catheterization with IVF and provide cumulative reproductive outcomes over long-term follow-up. STUDY FUNDING/COMPETING INTEREST(S): No funding was required and the authors have no competing interests to declare. REGISTRATION NUMBER: N/A